MicroRNA-513b-5p inhibits epithelial mesenchymal transition of colon cancer stem cells through IL-6/STAT3 signaling pathway - Zefeng Zhang; Weihong Sha (Discover Oncology, 2024)
Abstract Objective To reveal the mechanisms by which miR-513b-5p inhibits metastasis of colon cancer stem cells (CCSCs) through IL-6/STAT3 in HCT116 cells. Methods Sphere formation media and magnetic cell sorting were used to enrich and screen CCSCs. We used a colony formation assay, cell proliferation and viability assays, and a nude mouse transplantation tumor assay to identify CCSCs. ELISA was performed to identify IL-6 in the cell culture medium, and the growth, viability, wound healing, and transwell migration of distinct cell groups were compared to differentiate them. Dual-luciferase reporter assay, RT-PCR, and/or Western Blot analysis were conducted to determine the correlation between them. Results CD133+CD44+ HCT116 cells were shown to have higher cloning efficiency, greater proliferation ability and viability, and stronger tumorigenicity. A dual-luciferase reporter assay revealed that miR-513b-5p negatively affected STAT3 expression. RT-PCR and/or Western Blot analysis suggested that miR-513b-5p negatively affected STAT3 and Vimentin, while positively affecting E-cadherin expression. The STAT3 overexpression vector + miR-513b-5p inhibitor cell group had the highest efficiency, greatest proliferation ability and viability, and the highest IL-6 level in the experiments. Conclusions Mir-513b-5p inhibited the epithelial-mesenchymal transition (EMT) of CCSCs through IL-6/STAT3. This potential mechanism may provide a new therapeutic target for colon cancer.